2018
DOI: 10.1509/jim.17.0016
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Contingent Electronic Word-of-Mouth Signaling and Screening: A Comparative Study of Product Reviews in the United States and Japan

Abstract: Electronic word of mouth (eWOM) is an important source of influence on consumer decision making, yet little is known about cross-cultural differences in both the occurrence of eWOM and the relationship between eWOM and sales. The authors draw on signaling theory to develop a conceptual model and assess the relationships between country and the occurrence of eWOM, as well as between online ratings and relative product sales according to country. Online reviews and sales rank data for books, CDs, and DVDs were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…Indeed, we chose not to include cultural factors, as previous studies have not unveiled significant influences of culture on nostalgia effects (Hepper et al 2014;Steenkamp et al 1999). Nevertheless, given the presence of cultural differences across countries with respect to long-term orientation (Gürhan-Canli et al 2018;Hofstede and Minkov 2010;Lin and Kalwani 2018), it would be interesting for future research to examine whether certain specific cultural dimensions (e.g., long-term orientation) affect the nostalgic brand relationship dimension of brand authenticity (which relates to the temporal distance aspect of construal theory). By comparing developed Western countries with Eastern emerging markets, future researchers could investigate the influence of culture as well as the interaction of culture and country development on the effects of nostalgic brand positioning on brand equity.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Indeed, we chose not to include cultural factors, as previous studies have not unveiled significant influences of culture on nostalgia effects (Hepper et al 2014;Steenkamp et al 1999). Nevertheless, given the presence of cultural differences across countries with respect to long-term orientation (Gürhan-Canli et al 2018;Hofstede and Minkov 2010;Lin and Kalwani 2018), it would be interesting for future research to examine whether certain specific cultural dimensions (e.g., long-term orientation) affect the nostalgic brand relationship dimension of brand authenticity (which relates to the temporal distance aspect of construal theory). By comparing developed Western countries with Eastern emerging markets, future researchers could investigate the influence of culture as well as the interaction of culture and country development on the effects of nostalgic brand positioning on brand equity.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Various online brand communities can also help firms to identify and exploit lucrative opportunities in foreign markets through the provision of valuable information that facilitates, for instance, better understanding of consumer buying habits and preferences, the various stages of the purchasing process of foreign buyers, the acceptability of new product concepts, and the effectiveness of advertising messages (Baldus, Voorhees, and Calantone 2015; Gruner, Homburg, and Lukas 2014; Gürhan-Canli, Sarial-Abi, and Hayran, 2018). On the other hand, foreign buyers can interact with these communities to learn more about the firm's goods and services through information gained from other customers, discussions exchanged between community members, and positive comments deliberately posted by the firm to support its products and offerings in foreign markets (Essamri, McKechnie, and Winklhofer 2018;Lin and Kalwani 2018).…”
Section: Foreign Buyer Behaviormentioning
confidence: 99%
“…Theirs is the only study that focuses on at least one of the dimensions of the CE framework. Other studies have indicated that cultural differences affect word-of-mouth behavior (Lin and Kalwani 2018), the purposes for which people use social media (Lin and Kalwani 2018;Papacharissi and Rubin 2000), and so on. However, no study has shown the impact of cultural dimensions on the other dimensions of the CE framework.…”
Section: Literature Reviewmentioning
confidence: 99%